PROBABILISTIC MODELS FOR RELIABILITY ASSESSMENT OF PIPELINE SYSTEMS - Litvinov, А.; Gavrilenko, І.; Chinykov, N. (Municipal economy of cities (Technical science), 2022)
The issues of functional reliability assessment within the framework of the pipeline system reliability diagnostics subsystem are considered. The basis for the development of the functional reliability diagnostics subsystem is the breakdown of the pipeline system into emergency repair zones, as well as the replacement of the structure with the macro structure of emergency repair zones, which completely inherits the functional reliability of the system. A mathematical model is formed for each consumer Oi of the pipeline system, where and is the total number of consumers. If several consumers receive the target product from only one zone, then the corresponding mathematical models of functional reliability coincide. The following initial data are used to form a mathematical model of functional reliability in relation to the consumer Oi: calculation model of functional reliability in relation to all consumers. On the basis of emergency repair zones probabilistic models for calculating the functional reliability of pipeline systems have been developed, which are used in the algorithm for calculating the reliability of the entire system. The reliability of pipeline systems at the operational stage is supported by timely prevention and elimination of failures. A probabilistic model has been developed that makes it possible to assess the characteristics of the process of prevention and elimination of failures, to select the optimal parameters. Corresponding numerical calculations have been carried out. From the standpoint of a specialized organization that serves pipeline system, you need to minimize costs, while adhering to certain restrictions, namely: the deviation of the actual time of repair from the normative should not exceed the value, and all requests to eliminate accidents must be fulfilled. This means that the organization has a certain margin of capacity to service emergency calls. Minimize costs within the developed model can be solely due to the number of teams nmin, aiming at their maximum loading. So, we got the mathematical programming problem, which is: to find nmin, which maximizes the load function when the relevant restrictions are met.